Different Ly antigen phenotypes of in vitro induced helper and suppressor cells. - Feldmann, M; Beverley, P; Dunkley, M; Kontiainen, S (1975)
Specific T suppressor cells induced in vitro have a different Ly alloantigen phenotype from T helper cells induced in vitro from the same spleen cell pool. This study demonstrated that specific T suppressor cells differ from specific T helper cells, even if both are induced from the same spleen cell pool, in similar in vitro conditions, and directed to the same antigen, keyhole limpet haemocyanin. This has three implications. First, it demonstrates that the mechanism of specific T cell suppression, in this (but not in the other) model, is not due to excess help. Second, it provides a means of selectively manipulating T cell effects in antibody production (treatment with anti Ly 2 antiserum has been shown to augment helper activity in vitro). Third, the data increase the evidence that differentiated T effector cells have distinctive Ly phenotypes. The relationship of the specific suppressor cells described here to cytotoxic T cells, with the same Ly phenotype, and to nonspecific suppressor cells characterised as Ly 1+2+, remains to be clarified.